2015
DOI: 10.1002/joc.4558
|View full text |Cite
|
Sign up to set email alerts
|

Possible relation of the western North Pacific monsoon to the tropical cyclone activity over western North Pacific

Abstract: This study examined the relationship between the western North Pacific monsoon (WNPM) and the tropical cyclone (TC) activity over western North Pacific during the summer (June to August) in a period from 1977 to 2013. According to the western North Pacific monsoon index (WNPMI), 10 years with high indices (referred to as the positive WNPMI phase) and 10 years with low indices (referred to as the negative WNPMI phase) were chosen. TCs frequently formed in the southeast quadrant of the subtropical western North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…The WNP summer monsoon (WNPSM) is considered to be one of the most important large-scale systems for breeding boreal summer (June-August) WNP TC genesis. Previous studies have suggested that about 70% of the total number of WNP TCs are associated with the WNP monsoon trough (WNPMT) (Gray 1968;Frank 1987;McBride 1995;Ritchie and Holland 1999;Harr and Chan 2005;Chen et al 2006;Wu et al 2012;Molinari and Vollaro 2013;Zong and Wu 2015a,b;Choi et al 2016;Wang and Wu 2018). The importance of the WNPMT on TC genesis has been largely explained by two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…The WNP summer monsoon (WNPSM) is considered to be one of the most important large-scale systems for breeding boreal summer (June-August) WNP TC genesis. Previous studies have suggested that about 70% of the total number of WNP TCs are associated with the WNP monsoon trough (WNPMT) (Gray 1968;Frank 1987;McBride 1995;Ritchie and Holland 1999;Harr and Chan 2005;Chen et al 2006;Wu et al 2012;Molinari and Vollaro 2013;Zong and Wu 2015a,b;Choi et al 2016;Wang and Wu 2018). The importance of the WNPMT on TC genesis has been largely explained by two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…The WNP subtropical high and WNP summer monsoon could have profound effects on WNP TC activities [24,[37][38][39][40][41]. The observed changes of low-level atmospheric circulations (Figures 4 and 5) may be closely related to the changes of WNP subtropical highs and monsoons.…”
Section: Changing Tendencies In Wnp Subtropical High and Monsoonmentioning
confidence: 90%
“…The above result suggests that the anomalous anticyclone strengthened in the mid-latitude region of East Asia during high TCGF years implies weakening of the EASM, and the anomalous cyclone strengthened in the WNP implies the strengthening of the WNPSM. Regarding this, Choi et al (2016) have found that when the WNPSM is strengthened, the TCGF increases, but the EASM tends to be weakened.…”
Section: Easm and Wnpsmmentioning
confidence: 95%